The Effect of COVID-19 On Education - Amat, Salleh (International Journal of Human and Health Sciences (IJHHS), 2022)
COVID-19 affects various aspects of human life. This presentation will focus on the impact of COVID- 19 on education in Malaysia. In general, the COVID-19 pandemic has affected the teaching and learning for students that include preschool, primary school, secondary school, and higher education. Furthermore, the assessment system, especially the national examination was affected due to this pandemic. However, indirectly, this pandemic has also helped to speed up technology in the learning process. Online learning or home learning-based (PdPR) has been introduced. However, this PdPR had a psychological impact on students and teachers. Therefore, to ensure the effectiveness of this PdPR, all parties need to understand the importance of human connection and not just focus on the internet connection alone. Finally, it is also necessary to consider the need for practical work or lab work that requires practical training. This is especially important at tertiary education for programs that involve accreditation from professional bodies. This pandemic has also provided an opportunity for teachers, parents, and the community to work together in providing social or psychological support to students to facilitate the teaching and learning process. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S8